Antitrust law : economic theory and common law evolution - Hylton, Keith N. (Cambridge University Press, 2003)
This book is an effort to consolidate several different perspectives on antitrust law. Specific topics covered include perfect competition versus monopoly, enforcement, cartels, section 1 doctrine, rule of reason, agreement, boycott, power, vertical restraints, tying and exclusive dealing, horizontal mergers, and conglomerates.